Scanning Electron Microscopy Findings With Energy-Dispersive X-ray Investigations of Cosmetically Tinted Contact Lenses. Issue 5 (September 2015) - Hotta, Fumika; Eguchi, Hiroshi; Imai, Shoji; Miyamoto, Tatsuro; Mitamura-Aizawa, Sayaka; Mitamura, Yoshinori
<x xml:space="preserve">Abstract</x> Objective: To investigate the surfaces and principal elements of the colorants of cosmetically tinted contact lenses (Cos-CLs). Methods: We analyzed the surfaces and principal elements of the colorants of five commercially available Cos-CLs using scanning electron microscopy with energy-dispersive x-ray analysis. Results: In two Cos-CLs, the anterior and posterior surfaces were smooth, and colorants were found inside the lens. One lens showed colorants located to a depth of 8 to 14 μm from the anterior side of the lens. In the other lens, colorants were found in the most superficial layer on the posterior surface, although a coated layer was observed. The colorants in the other three lenses were deposited on either lens surface. Although a print pattern was uniform in embedded type lenses, uneven patterns were apparent in dot-matrix design lenses. Colorants used in all lenses contained chlorine, iron, and titanium. In the magnified scanning electron microscopy images of a certain lens, chlorine is exuded and spread. Conclusions: Cosmetically tinted contact lenses have a wide variety of lens surfaces and colorants. Colorants may be deposited on the lens surface and consist of an element that has tissue toxicity.